Drosophila melanogaster as a suitable in vivo model to determine potential side effects of nanomaterials: A review. (17th February 2016) - Alaraby, Mohamed; Annangi, Balasubramanyam; Marcos, Ricard; Hernández, Alba
ABSTRACT: Despite being a relatively new field, nanoscience has been in the forefront among many scientific areas. Nanoparticle materials (NM) present interesting physicochemical characteristics not necessarily found in their bulky forms, and alterations in their size or coating markedly modify their physical, chemical, and biological properties. Due to these novel properties there is a general trend to exploit these NM in several fields of science, particularly in medicine and industry. The increased presence of NM in the environment warrants evaluation of potential harmful effects in order to protect both environment and human exposed populations. Although in vitro approaches are commonly used to determine potential adverse effects of NM, in vivo studies generate data expected to be more relevant for risk assessment. As an in vivo model Drosophila melanogaster was previously found to possess reliable utility in determining the biological effects of NM, and thus its usage increased markedly over the last few years. The aims of this review are to present a comprehensive overview of all apparent studies carried out with NM and Drosophila, to attain a clear and comprehensive picture of the potential risk of NM exposure to health, and to demonstrate the advantages of using Drosophila in nanotoxicological investigations.